2019
DOI: 10.3390/ijms20061475
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Pathogenesis and Treatment

Abstract: Research on psoriasis pathogenesis has largely increased knowledge on skin biology in general. In the past 15 years, breakthroughs in the understanding of the pathogenesis of psoriasis have been translated into targeted and highly effective therapies providing fundamental insights into the pathogenesis of chronic inflammatory diseases with a dominant IL-23/Th17 axis. This review discusses the mechanisms involved in the initiation and development of the disease, as well as the therapeutic options that have aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1,265
0
75

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,391 publications
(1,343 citation statements)
references
References 217 publications
3
1,265
0
75
Order By: Relevance
“…Psoriasis is a chronic inflammatory skin disease characterized by the hyperproliferation of keratinocytes and infiltration of inflammatory cells. It affects about 2% of the population worldwide, but the rate varies according to region [1]. The molecular mechanisms of psoriasis are complicated and unclear, but many studies have indicated that psoriasis is an immune-mediated disease.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory skin disease characterized by the hyperproliferation of keratinocytes and infiltration of inflammatory cells. It affects about 2% of the population worldwide, but the rate varies according to region [1]. The molecular mechanisms of psoriasis are complicated and unclear, but many studies have indicated that psoriasis is an immune-mediated disease.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory skin condition that is also likely manifested in patients with a genetic predisposition who are acted on by exogenous factors. While there are various subtypes of psoriasis, all are characterized by erythematic, and often pruritic, plaques . Psoriasis is predominantly thought to be caused by an inappropriate activation of the cutaneous immune system against a perceived pathogen .…”
Section: Addressing the Skin Microflora To Combat Disease Statesmentioning
confidence: 99%
“…Psoriasis is treated by conventional drugs such as methotrexate, cyclosporine, retinoids and dimethyl fumarate and apremilast or by biologics such as anti TNF-α and IL23/IL17 blockers [1,2,3] ; however, in such treatments there are limitation suggesting the wisdom to develop new interventions [4,5,6] .…”
Section: Introductionmentioning
confidence: 99%